Arteriovenous fistula rescue thrombosed prosthetics - Dutto, Gabriel; López Chapuis, Daniel; Esperón, Alejandro; Gastambide, Carmelo (Cirugía del Uruguay, 1998)
The authors ana!yse the results of 21 rescue procedures of thrombosed arterio-venous fístulas (AVF) in 1 O patíents, obtaining a high global percentage of rescue (76%) in spíte of the thrombosis in sorne cases. Effectiveness was greater when thrombectomy was accompanied by correction of anatomical abnormalities general/y situated at the leve/ of the venous anastomosis. The authors poínt out the importance of identifyíng anatomica/ abnormalitíes in the A VF, mainly by mea ns of intraoperative phlebography, and its treatment simu/taneous to thrombectomy.